1994
DOI: 10.1007/bf00403375
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vanadyl treatment on vascular responsiveness of streptozotocin-diabetic rats

Abstract: Summary Vanadyl sulphate has been demonstrated to possess insulin-like effects in streptozotocin (STZ) diabetic rats, including the normalization of hyperglycaemia and the prevention of diabetes-induced cardiac dysfunction. However, the effectiveness of vanadyl sulphate on diabetes-related vascular aberrations has not been questioned. Hence, in the present work, we have specifically addressed the question of whether chronic oral vanadyl sulphate treatment has any beneficial effect on diabetes-induced changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 48 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…First, the results of the present study demonstrated that endothelium intact and denuded aortic rings from STZ‐diabetic rats are more responsive to the contractile effects of α 1 ‐adrenoceptor agonists like PE than aortic rings from corresponding (non‐diabetic) controls. Similar results showing an increased vascular responsiveness to contractile agents in STZ‐diabetic rats have been reported in previous studies 18,19 . It is well‐known that, in the diabetic state, there is an enhanced oxidative stress due to excessive production of oxygen free radicals and decreased potential of anti‐oxidant defence systems 20,21 .…”
Section: Discussionsupporting
confidence: 84%
“…First, the results of the present study demonstrated that endothelium intact and denuded aortic rings from STZ‐diabetic rats are more responsive to the contractile effects of α 1 ‐adrenoceptor agonists like PE than aortic rings from corresponding (non‐diabetic) controls. Similar results showing an increased vascular responsiveness to contractile agents in STZ‐diabetic rats have been reported in previous studies 18,19 . It is well‐known that, in the diabetic state, there is an enhanced oxidative stress due to excessive production of oxygen free radicals and decreased potential of anti‐oxidant defence systems 20,21 .…”
Section: Discussionsupporting
confidence: 84%
“…[4] It was reported that enhanced contractile responses of STZ-diabetic rat aorta to α-adrenergic agonists as noradrenaline are largely dependent on the presence of extracellular Ca ++ , increased adrenergic stimulation, phosphoinositide metabolism, Ca ++ channels sensitivity, deficiency of endothelial activity and/or decreased calmodulin levels. [1618] In this study, by evaluation of increased response to PE of STZ-diabetic rat aorta, it was supposed that 6-week STZ-induced diabetes changed the α-adrenergic receptor number and/orthe mechanisms which were mentioned above without changing receptor affinity. However, muscarinic receptor affinity, number or post-receptor pathways remained unchanged.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results showing the increased vascular responsiveness to contractile agents in STZ-diabetic rats have been reported in many previous studies. [910] This increased vascular smooth muscle responsiveness in diabetic rats could be attributed to deficient endothelial activity,[910] enhanced phosphoinositide (PI) metabolism,[11] enhanced sensitivity of calcium channels,[7] and increased sensitivity to adrenergic agonists. [12] Furthermore, oxidative stress is increased due to excessive production of oxygen free radicals and decreased antioxidant defense systems.…”
Section: Discussionmentioning
confidence: 99%